Mograph Cinema 4d untuk Menunjang Efek Visual Video Klip - Ardiyan, Ardiyan; Ardiyansah, Ardiyansah; Mahardhika, Satrya (Bina Nusantara University, 2010)
This research is to talk about the advantages of MoGraph as one reliability feature in 3D modeling application, 4D Cinema as the implemented example in Cinta Laura video clip. The advantage in MoGraph is the ability to create multiple object moving effect accordingly and (or) randomly easily and efficiently, also supported by the render quality of Cinema 4D that clean and relatively fast. The advantage made MoGraph Cinema 4D is suitable to use to enrich the visual effect a motion graphic work. The quality is hoped to support MoGraph usage as more creative. Regarding today’s visual variation is effected by the digital technology development, therefore the implementation of MoGraph Conema 4D is hoped to be optimally supporting creativity in making video clip in motion graphic art content.